Peran Mahkamah Agung dalam Menegakkan Prinsip Keadilan dalam Sistem Peradilan Indonesia - Dimas Gibran Satrio Utomo (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The Supreme Court (Mahkamah Agung or MA) plays a central role in upholding the principle of justice as the final stronghold in Indonesia's judicial system. This article examines the role of the MA in ensuring substantive justice, efficiency, and transparency in judicial processes, as well as its contribution to the development of law and public policy. Using a qualitative review analysis approach, the discussion explores the MA’s functions in case resolution, safeguarding integrity, improving accessibility through technologies like e-court, and addressing globalization challenges. This article also highlights the MA's protection for vulnerable groups, such as indigenous communities and victims of discrimination, and its responses to cross-border issues like cybercrimes and human rights violations. The conclusion reveals that while the MA has made significant progress in enforcing the law, challenges such as case overload, perceptions of corruption, and gaps in access to justice remain critical concerns. Continuous reforms, enhancing judges' professionalism, and technological innovation are key measures to ensure the MA remains relevant and effective in delivering substantive justice for society.